Experimental investigation of machining parameters on surface roughness in dry and wet wire-electrical discharge machining - Abdulkareem, Suleiman; Khan, Ahsan Ali; Mohd Zain, Zakaria (Trans Tech Publications, 2011)
Wire electrical discharge machining (WEDM) is a thermal process in which the workpiece and the wire (tool) experience an intense local heating in the discharge channel. The high power density results in the erosion of a part of the material from both electrodes by local melting and vaporization. Whilst good surface finish and high material removal rate of the workpiece is a major requirement, the effect of EDM machining factors on these requirements cannot be overlooked. This study investigate the effect of two different machining methods of dry and wet WEDM process as well as the effect of on-time and voltage on the surface roughness of the workpiece. The machining factors used for this study are the pulse current, on-time and voltage. The results of the effect of the two machining methods on the responses are investigated and reported in this paper.